2009
DOI: 10.18388/abp.2009_2452
|View full text |Cite
|
Sign up to set email alerts
|

Fungi pathogenic to humans: molecular bases of virulence of Candida albicans, Cryptococcus neoformans and Aspergillus fumigatus.

Abstract: The frequency of severe systemic fungal diseases has increased in the last few decades. The clinical use of antibacterial drugs, immunosuppressive agents after organ transplantation, cancer chemotherapy, and advances in surgery are associated with increasing risk of fungal infections. Opportunistic pathogens from the genera Candida and Aspergillus as well as pathogenic fungi from the genus Cryptococcus can invade human organism and may lead to mucosal and skin infections or to deep-seated mycoses of almost all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
133
0
17

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(152 citation statements)
references
References 110 publications
2
133
0
17
Order By: Relevance
“…However, it contains a laccase enzyme which is capable of making melanin from a wide variety of substrates (Garcia-Rivera et al 2005). As a consequence, C. neoformans is melanized in infections, and the ability to melanize is an important virulence factor for C. neoformans as well as several other human pathogenic fungi (Karkowska-Kuleta et al 2009). Melanin in C. neoformans is located in the cell wall, and is thought to provide protection from a variety of environmental insults, including UV light, desiccation, toxic metals, and attack by the reactive oxygen species produced by the macrophages (reviewed in Gomez &Casadevall 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, it contains a laccase enzyme which is capable of making melanin from a wide variety of substrates (Garcia-Rivera et al 2005). As a consequence, C. neoformans is melanized in infections, and the ability to melanize is an important virulence factor for C. neoformans as well as several other human pathogenic fungi (Karkowska-Kuleta et al 2009). Melanin in C. neoformans is located in the cell wall, and is thought to provide protection from a variety of environmental insults, including UV light, desiccation, toxic metals, and attack by the reactive oxygen species produced by the macrophages (reviewed in Gomez &Casadevall 2003).…”
Section: Introductionmentioning
confidence: 99%
“…An Afatg1 mutant showed compromised sporulation, which could be restored by supplementation of exogenous nitrogen source (ammonium tartrate) [52]. The reason behind variant requirements for autophagy in these four pathogens was discussed systematically in a recent review [89], and was indicated to be based on the difference in the aspects such as the host infection niche and the evolutionary pressures faced by the pathogen species [89], the host signals in response to the pathogen [89], and molecular basis of virulence for each pathogen [90]. …”
Section: Autophagy In Opportunistic Human Fungal Pathogensmentioning
confidence: 99%
“…An altered balance between the host immunity and this opportunistic fungus, as in the case of immunocompromised patients, is one of the leading causes of candidiasis in humans (Bodey, 1993). After entering the blood stream, the yeast cells can infect all internal organs and may cause life-threatening septicemia (Karkowska-Kuleta et al, 2009). Candidiasis can develop as superficial candidiasis (skin and mucosa) which occurs in healthy individuals, or invasive candidiasis which is seen in cancer patients, AIDS patients, and immunocompromised individuals following transplantation (Larriba et al, 2000).…”
Section: Introductionmentioning
confidence: 99%